2015
DOI: 10.1016/j.jfma.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, microbiology, and outcomes for patients with lung and disseminated nocardiosis in a tertiary hospital

Abstract: These results highlight the protean disease manifestations and antimicrobial susceptibility of Nocardia and indicate the need to address the option of combined antimicrobial therapy for lung and disseminated nocardiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
0
20
1
4
Order By: Relevance
“…[9] Despite appropriate therapy, the overall mortality rate is high due to delay in diagnosis or to the debilitated state of patients with severely compromised host defences. Wang et al [3] showed that the mortality from lung nocardiosis in their cohort was 33%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[9] Despite appropriate therapy, the overall mortality rate is high due to delay in diagnosis or to the debilitated state of patients with severely compromised host defences. Wang et al [3] showed that the mortality from lung nocardiosis in their cohort was 33%.…”
Section: Discussionmentioning
confidence: 95%
“…The most common species are N. asteroides and N. brasiliensis. [3,4] Transmission in humans is by direct skin inoculation or inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution CT (HRCT), which can depict lung structures and pathogenic changes with excellent details, is often used to evaluate pulmonary parenchyma and interstitial abnormalities (18)(19)(20). Comparing to conventional radiography, HRCT can detect pathologic changes of pulmonary nocardiosis at early phase and in better characteristics (5,6). In a pictorial review, Kanne et al illustrated that CT findings of pulmonary nocardiosis included lung consolidation, nodules/masses, pleural involvement and chest wall extension (9).…”
Section: Discussionmentioning
confidence: 99%
“…Because its clinical presentations are nonspecific as subacute pneumonia, pulmonary nocardiosis is difficult to diagnose. If correct diagnosis can be obtained, pulmonary nocardiosis respond favorably to high-dose sulfonamide therapy, otherwise, hematogenous dissemination to soft tissue and brain is association with high morbidity and mortality (5)(6)(7). Therefore, prompt diagnosis and treatment is essential for improving patients' outcome.…”
Section: Introductionmentioning
confidence: 99%